Successful campus outreach for academic libraries building community through collaboration - Keeran, Peggy 1959-; Forbes, Carrie 1975- (Rowman & Littlefield, 2018)
In Successful Campus Outreach for Academic Libraries: Building Community Through Collaboration, Peggy Keeran and Carrie Forbes bring together a variety of ways academic libraries are engaging with their communities through outreach, with creativity and the spirit of collaboration as major themes throughout. As a compendium of best practices, it serves as a resource for academic librarians to discover new programming ideas, to learn principles of effective marketing, and to help them think strategically and programmatically about outreach activities of all types.--Provided by publisher.